ENHANCING WASTEWATER TREATMENT EFFICIENCY USING MICROBIAL FUEL CELLS: A STUDY ON DOMESTIC AND HOSPITAL SEWAGE - Bilal A. Alarabi; Rand Salwan Numan; Hiba Hamad Mohammed (European Science Publishing, 2025)
This study evaluates the efficiency of microbial fuel cells in treating domestic and hospital wastewater, focusing on pollutant removal, bioelectricity production, and microbial communities.
Keywords: Microbial fuel cells, wastewater treatment, bioelectricity, pollutant removal, IMViC profiling.